2012
DOI: 10.1007/s10295-012-1086-0
|View full text |Cite
|
Sign up to set email alerts
|

Malt-induced premature yeast flocculation: current perspectives

Abstract: Premature yeast flocculation (PYF) is a sporadic problem for the malting and brewing industries which can have significant financial and logistical implications. The condition is characterised by abnormally heavy (and sometimes early) flocculation of yeast during brewery fermentations. The resulting low suspended yeast cell counts towards the end of the fermentation can result in flavour defects and incomplete attenuation (fermentation of sugars to alcohol). Despite several decades of research into the phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…This normally occurs at the end of fermentation, as sugars present during early fermentation associate with the lectin surface, preventing interaction (180). In PYF, yeast aggregation and settling occur prior to full attenuation of sugar, resulting in incomplete fermentation, off-flavors, and significantly decreased beer quality (181)(182)(183). PYF can be initiated by a range of polysaccharides naturally occurring in the barley husk (183)(184)(185), released either in response to microbial infection or by degradation of the husk by microbial enzymatic activity (186).…”
Section: Barleymentioning
confidence: 99%
“…This normally occurs at the end of fermentation, as sugars present during early fermentation associate with the lectin surface, preventing interaction (180). In PYF, yeast aggregation and settling occur prior to full attenuation of sugar, resulting in incomplete fermentation, off-flavors, and significantly decreased beer quality (181)(182)(183). PYF can be initiated by a range of polysaccharides naturally occurring in the barley husk (183)(184)(185), released either in response to microbial infection or by degradation of the husk by microbial enzymatic activity (186).…”
Section: Barleymentioning
confidence: 99%
“…These polysaccharides can act as a bridge between cells by interacting with yeast lectin-like proteins. It has been suggested that the binding between these polysaccharides and yeast cells is mediated by cationic antimicrobial peptides [22]. These compounds are produced by barley to protect against microbial atack, or in response to fungal contamination during the malting process.…”
Section: +mentioning
confidence: 99%
“…Recent studies have found that nitrogen starvation induces flocculation in bottom‐fermenting yeast. Both fungi and malt have also been implicated in premature yeast flocculation .…”
Section: Yeast Flocculation and Cell Wall Structure And Functionmentioning
confidence: 99%